Automated Deduction – CADE 29: 29th International Conference on Automated Deduction, Rome, Italy, July 1–4, 2023, Proceedings - Pientka, Brigitte; Tinelli, Cesare (Lecture Notes in Computer Science; Lecture Notes in Artificial Intelligence, 2023)
This open access book constitutes the proceedings of the 29th International Conference on Automated Deduction, CADE 29, which took place in Rome, Italy, during July 2023. The 28 full papers and 5 short papers presented were carefully reviewed and selected from 77 submissions. CADE is the major forum for the presentation of research in all aspects of automated deduction, including foundations, applications, implementations, and practical experience. The papers are organized in the following topics: Logical foundations; theory and principles; implementation and application; ATP and AI; and system descriptions.